Attitudes towards and knowledge about intrauterine contraceptive devices among women in the reproductive age group in a resourceconstrained setting - Pierre Monji Builu; Thinagrin Dhasarathun Naidoo (South African Medical Association, 2015)
Background. One of the strategies to reduce maternal mortality includes accessible and appropriate contraceptive services to all women. The intrauterine contraceptive device (IUCD) has been identified as a cheap and effective means of contraception by the South African National Department of Health.Objective. To explore knowledge about the IUCD among women using the public health sector and identify any misconceptions.Methods. A sample of 150 women attending antenatal/postnatal clinics were interviewed using a structured questionnaire.Results. Forty-six percent (n=69) had some experience with the injectable form of contraception, and 2.7% (n=4) had used the IUCD; 70.7% (n=106) knew that the device does not prevent HIV transmission, 40.7% (n=61) knew that HIV-positive women can use the IUCD, 75.3% (n=113) believed that the IUCD causes heavy bleeding, 36.7% (n=55) knew that the device does not stop fertility indefinitely, 33.3% (n=50) knew that the IUCD can be inserted in the immediate postpartum period, and 26.7% (n=40) knew that the duration of use is 10 years. In terms of attitudes, 40.0% (n=60) expressed concern about the pain during insertion, 33.3% (n=50) believed the IUCD can cause cancer, and 32.0% (n=48) believed that the device interferes with normal sexual activities. Most participants 77.3% (n=116) acquired the information they had about the IUCD from the clinic during teaching and counselling sessions.Conclusion. This survey documented poor knowledge about the IUCD among women using the public health sector. However, the fact that there are few misconceptions and that clients rely on the clinic information should be seen as an opportunity to improve the situation.Â